Integrasi Pendidikan Digital dan Ekonomi Kreatif melalui Program Digitalisasi Pendaftaran Lokasi Usaha di Google Maps yang Berada di Desa Timbang Lawan - Pandi Ahmad Jawara; Apriani Syahputri; Afriani Afriani; Dion Wirayuda Bahri; Ilka Zufria (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the implementation of the digitalization program for business location registration on Google Maps as a form of digital education integration and strengthening the creative economy in Timbang Lawan Village. The background of this research departs from the low public understanding of the use of digital technology for local business development, which has an impact on the limited market reach, promotion, and competitiveness of MSMEs. The method used in community service is Participatory Action Research (PAR). The PAR method was chosen because it emphasizes active collaboration between researchers and the community so that the resulting solutions are more in line with local needs and can be applied sustainably. The results of the activity show that there is an increase in digital literacy among business actors, especially in the use of digital maps for promotion. Based on documentation, observations, and interviews, a number of MSMEs have successfully registered their business locations on Google Maps, verified by Google, and have begun to receive benefits in the form of increased business visibility, customer numbers, and opportunities for product development and wider business networks at the regional level.